2015
DOI: 10.1515/amcs-2015-0046
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic analysis assessment in speech pathology detection

Abstract: Automatic detection of voice pathologies enables non-invasive, low cost and objective assessments of the presence of disorders, as well as accelerating and improving the process of diagnosis and clinical treatment given to patients. In this work, a vector made up of 28 acoustic parameters is evaluated using principal component analysis (PCA), kernel principal component analysis (kPCA) and an auto-associative neural network (NLPCA) in four kinds of pathology detection (hyperfunctional dysphonia, functional dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 46 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…In recent years, machine learning methods have been very popular and effective in solving problems in various fields [37][38][39][40][41][42][43][44]. Thus, to classify the extracted features, the MATLAB 2016a classification learner toolbox was used.…”
Section: The Used Definitions For the Proposed Methodsmentioning
confidence: 99%
“…In recent years, machine learning methods have been very popular and effective in solving problems in various fields [37][38][39][40][41][42][43][44]. Thus, to classify the extracted features, the MATLAB 2016a classification learner toolbox was used.…”
Section: The Used Definitions For the Proposed Methodsmentioning
confidence: 99%
“…To compare linear reduction method, 2 non-linear transformation methods were used: non-linear PCA (NLPCA) based on neural networks and kernel PCA (kPCA) with the usage of Gauss kernel function. PCA, kPCA and NLPCA methods were already described in our previous work [1].…”
Section: Methodsmentioning
confidence: 99%
“…There is still a challenge in finding new features that could discriminate between normal and pathological voices or even assess their quality, but also find different approaches on classification [1]- [6]. Voice pathology detection by the usage of acoustic signal processing can be measured, described qualitatively and quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Vast majority of studies focus on combining various features without any physiological reasoning. Extensive and summarized reviews on acoustic analysis of pathological voice can be found in Arroyave et al (2012), Vaičiukynas et al (2015), Panek et al (2015).…”
Section: Acoustic Speech Analysis For Voice Disordersmentioning
confidence: 99%